Reliability of phase-specific outcome measurements in change-of-direction tests using a motorized resistance device - Frederic Westheim; Øyvind Gløersen; Damian Harper; Håkon Laugsand; Ola Eriksrud (Frontiers in Sports and Active Living, 2023)
This study aims to determine test-retest reliability of phase-specific information during initial acceleration, deceleration, and re-acceleration phases of different change-of-direction (CoD) tests using a motorized resistance device (MRD). A total of 21 participants (16 males and five females, with mean age of 22.3 ± 3.9 years, body mass of 75.2 ± 6.9 kg, height of 177.9 ± 6.8 cm) completed the modified 505 (m505), 10-0-5, and 15-0-5 CoD tests on four different test sessions while exposed to an external load (3 kg) provided by the MRD. Outcome variables included overall and phase-specific kinetic (force, power, and impulse) and kinematic (time, distance, velocity, and acceleration/deceleration) data during the initial acceleration, deceleration, and re-acceleration phases. The deceleration and re-acceleration phases were further divided into two subphases, namely, early and late subphases, using 50% of maximum velocity. Reliability was assessed using an intraclass correlation coefficient (ICC), coefficient of variation (CV), typical error (TE), and minimal detectable change (MDC). Good to excellent ICC values (>0.75) and acceptable (<10%) to good (<5%) CV values were observed for most outcome measurements. Specifically, 80.1% (822 out of 1,026) of all variables showed good or better relative reliability (i.e., ICC ≥ 0.75), while 97.0% (995 out of 1,026) of all variables showed acceptable or better absolute reliability (i.e., CV < 10%). In conclusion, the present study demonstrates that the MRD can obtain reliable phase-specific outcome measurements across different CoD tests, providing coaches and researchers with new opportunities to advance our understanding of CoD ability and inform more advanced CoD training prescriptions.